1997
DOI: 10.1006/jcss.1997.1520
|View full text |Cite
|
Sign up to set email alerts
|

Dyn-FO: A Parallel, Dynamic Complexity Class

Abstract: Traditionally, computational complexity has considered only static problems. Classical complexity classes such as NC, P, and NP are defined in terms of the complexity of checking upon presentation of an entire input whether the input satisfies a certain property. For many applications of computers it is more appropriate to model the process as a dynamic one. There is a fairly large object being worked on over a period of time. The object is repeatedly modified by users and computations are performed. We develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
163
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(170 citation statements)
references
References 28 publications
5
163
0
Order By: Relevance
“…Already with the introduction of the dynamic complexity framework, dynamic first-order programs for maintaining the reachability query for acyclic and undirected graphs have been known [DS95,PI97]. Later Hesse showed that reachability (on arbitrary graphs) can be maintained using TC 0 -circuits as update mechanism [Hes03a], where TC 0 -circuits are defined like AC 0 -circuits except that they can also use majority gates.…”
Section: Maintainability Of Basic Queriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Already with the introduction of the dynamic complexity framework, dynamic first-order programs for maintaining the reachability query for acyclic and undirected graphs have been known [DS95,PI97]. Later Hesse showed that reachability (on arbitrary graphs) can be maintained using TC 0 -circuits as update mechanism [Hes03a], where TC 0 -circuits are defined like AC 0 -circuits except that they can also use majority gates.…”
Section: Maintainability Of Basic Queriesmentioning
confidence: 99%
“…Already Patnaik and Immerman observed that regular languages can be maintained in DynFO [PI97]. A more extensive study of languages conducted by Gelade, Marquardt and Schwentick revealed that regular languages are exactly the languages that can be maintained in DynProp [GMS12].…”
Section: Maintainability Of Basic Queriesmentioning
confidence: 99%
See 3 more Smart Citations